2014
DOI: 10.1186/1750-1326-9-48
|View full text |Cite
|
Sign up to set email alerts
|

Oligomeric Aβ-induced synaptic dysfunction in Alzheimer’s disease

Abstract: Alzheimer’s disease (AD) is a devastating disease characterized by synaptic and neuronal loss in the elderly. Compelling evidence suggests that soluble amyloid-β peptide (Aβ) oligomers induce synaptic loss in AD. Aβ-induced synaptic dysfunction is dependent on overstimulation of N-methyl-D-aspartate receptors (NMDARs) resulting in aberrant activation of redox-mediated events as well as elevation of cytoplasmic Ca2+, which in turn triggers downstream pathways involving phospho-tau (p-tau), caspases, Cdk5/dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
289
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 461 publications
(297 citation statements)
references
References 162 publications
(179 reference statements)
6
289
0
2
Order By: Relevance
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although plaques and tangles have traditionally been regarded as the main histopathological hallmarks of AD, a large body of evidence accumulated over the past decade suggests that soluble forms of these proteins are sufficient to trigger the development of the neurotoxicity process in AD (Berger et al., 2007; Bittner et al., 2010; Chabrier, Cheng, Castello, Green & LaFerla, 2014; Forner et al., 2017; Guerrero‐Munoz, Gerson & Castillo‐Carranza, 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu, Okamoto, Lipton & Xu, 2014). These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…These studies have clearly shown that soluble Aβ and tau oligomers are toxic to synapses and that the accumulation of these soluble isoforms correlates significantly with synaptic and memory impairments (Berger et al., 2007; Bittner et al., 2010; Chabrier et al., 2014; Forner et al., 2017; Guerrero‐Munoz et al., 2015; Muller‐Schiffmann et al., 2016; Shankar et al., 2008; Spires‐Jones & Hyman, 2014; Tu et al., 2014). In addition, we have also demonstrated that Aβ oligomers modulate the development of tau pathology and accelerate cognitive and synaptic impairments (Chabrier et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…However soluble Aβ oligomers are considered the more toxic species (Dahlgren et al, 2002 and can induce neurotoxicity and memory deficits in mice (Brouillette et al, 2012). A widely supported hypothesis proposes that oligomeric Aβ induces the synaptic dysfunction and the spine loss that occurs in AD (Tu et al, 2014), and closely correlates with the severity of neurodegeneration (Terry et al, 1991, McLean et al, 1999. Synaptic loss mediated by…”
Section: 11b)mentioning
confidence: 99%
“…Aβ is in turn dependent on N-methyl-D-aspartate receptor (NMDA-R) activity and mediated by dysregulated redox events, elevated cytoplasmic Ca 2+ and tau hyperphosphorylation (Shankar et al, 2007, Ittner et al, 2010, Tu et al, 2014. A parsimonious conclusion is that the BFCN-lesion induced increase in hippocampal Aβ levels is due to increased soluble Aβ which may cause synaptic transmission dysfunction and/or spine degeneration to result (either directly, or perhaps in combination with reduced ACh modulation) in MWM task memory retention impairments.…”
Section: 11b)mentioning
confidence: 99%
See 1 more Smart Citation